Sumatran rhinoceros and wildlife survey East of Segama, Danum Valley, Sabah, Malaysia - M.T, Abdullah; Waidi, Sinun; Mathew, Daria; Sumbin, Gadas; Bernard, Henry; Gumpil, Jerry; Murray, L; Ola, Barnabos (Report to SWD/MTED/YS/WCS, 1995)
The purpose of this survey was to assess the Sumatran rhinoceros population occurring around DVFC on the eastern part of Sungai Segama, Sabah.